1983
DOI: 10.1002/qua.560230313
|View full text |Cite
|
Sign up to set email alerts
|

Quantum study of the ground state of a series of unsaturated boron–nitrogen compounds by the MNDO method. I. Geometries and stabilities

Abstract: A MNDO study of molecular geometries, enthalpies, formation, atomization, bond separation, and hydrogenation of a series of unsaturated boron-nitrogen compounds, linear with two and three members and cyclic with three, four, five, and six members are presented. For all these molecules, MNDO calculations are in excellent agreement with available ab initio calculations or experimental data. The high rotational barrier in aminoborane HlBNH2, 30.6 kcal/mol, and the length of bond in iminoborane HBNH, 1.1 83 A, imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
3
14
0
Order By: Relevance
“…Our results for benzene and borazine are identical with those of Dewar and co-workers [24,25]. However, in the report of Maouche and Gayoso [26], a heat of forma- tion of -130.8 kcal/mol was calculated for borazine, which is about 1% less negative than that calculated in our study.5…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results for benzene and borazine are identical with those of Dewar and co-workers [24,25]. However, in the report of Maouche and Gayoso [26], a heat of forma- tion of -130.8 kcal/mol was calculated for borazine, which is about 1% less negative than that calculated in our study.5…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we thought that MNDO would be an appropriate probe of the properties of the azaborines. Further, Maouche and Gayoso [26] report the MNDO study of a series of linear and cyclic unsaturated boron-nitrogen compounds and concluded that Chart II…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The PAPBAZ isomers 1 and 2 have apparently not been studied experimentally, and only one computational report [9] mentions these molecules. However, because the MNDO method has been shown [17, [25][26][27][28]] to be a reliable indicator of the ground-state properties of boron-nitrogen-containing molecules, there exists a solid basis upon which to establish the structures of these molecules. The PAPBAZ isomers 1 and 2 are calculated to be planar molecules, possibly containing n-systems at least as delocalized as in borazine.…”
Section: Discussionmentioning
confidence: 99%
“…The structures, stability, and reactivity of iminoborane were reviewed by Paetzold [5]. In the past three decades, iminoborane aroused considerably interest in several experimental and some theoretical studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%